P122 Treatment with rituximab to demand in rheumatoid arthritis. effectiveness analysis. (21st February 2018) - Julia, U; Fobelo, MJ; Guzman, M
Abstract : Introduction: Rituximab (RTX) is a chimeric anti-CD20 monoclonal antibody that has been shown to be effective in the treatment of rheumatoid arthritis (RA). At present we have different treatment regimens in terms of the time of administration, every 6 months or on demand and with respect to the dose used: cycles of 1000 mg x 2 or 500 mg x 2. Objectives: Our objetive was to analyse the effectiveness on- demand tratment regimen of RTX in RA Methods: Retrospective observational study on RA with RTX treatment between January 2006 and February 2015 was carried out. Administration was performed if DAS28 >3.2. The median time of retreatment and the number of patients portrayed at 8, 12, 16, 20 and 24 months were calculated Results: 57 patients were included, mean age 55 years, 70% women; 93% FR+, 31.6% ACPA +and 63.2% with erosive disease. The median time of evolution of RA at the start of RTX 8.1 years. All patients had high activity at the start of RTX [median DAS28=5.6; HAQ=1.75]. Prior to RTX, all patients were treated with another biological (24.5% with two or more). 56% of patients were receiving DMARDs. The median time of retreat was 7 months. The number of patients portrayed was: at 8 months 55.8%, at 12 months 69.4%, at 16 months 80%, at 20 months 81.3% and at 24 months at 88.6%. Those not evaluated in each quarter are those who are discontinued RTX before two years of follow-up (four due to inefficacy and one due to adverse reaction) or, at the time of completing the study, have not completed two years of treatment. The effectiveness considered as the median number of cycles received at two years was 2. Conclusions: Although the median time to retreatment was seven months, there are some patients who remain unplastered for about two years. 80% of the patients had been portrayed at 16 months, half with 1 cycle of RTX and the other half with 2. The pattern on demand even allowed to decrease the doses of concomitant DMARDs. A subsequent individualised analysis of patients will allow us to evaluate the possible characteristics that can affect the effectiveness of the pattern on demand Disclosure of interest: None declared